The Transmission of Fundamentalist Ideology in the Method of Legal Ijtihad: A Study of Ahmad Hassan's Interpretation of the Qur'an in the Book al-Furqon - Abd Muhaimin; Indal Abror (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
This article is the result of a literature review on the book